Traditional Medicinal plants Used for the Treatment of Cancer in Mubi, Adamawa State, Nigeria - Abdulrahman Dogara; Isah Labaran; Saber W. Hamad; Abubakar Abdullahi Lema; Bello Hassan Jakada (Al-Qadisiyah Journal of Pure Science, 2021)
Medicinal plants have aided in the establishment and expansion of the modern healthcare system. Plants with medicinal potential are still the only way forward, as their acceptance and recognition spread over the globe. Ethnobotany is an interdisciplinary field that studies how people use plants in their daily lives. Nigeria accounted for roughly 20% of Africa's population and slightly more than half of West Africa's projected 681,000 new cancer cases in 2008, accounting for roughly 20% of the continent's population and slightly more than half of West Africa's. For pharmaceutical exploration and conservation, it is important to document the use of medicinal plants in a specific region across time. The study's goal was to find out which plants were used to treat Cancer in Mubi, Northern eastern part of Nigeria. An open ended interview was employed with no sampling size selection. Used Value (UV), Fidelity level (FL) and Relative frequency of citation (RFC) were used to determine the most important and effective plants used for treatment of cancer. Ten plants were documented with Neolamarckia cadamba  has 0.9, 1 and 100 % of UV, RFC and FL, respectively. The study will serve as a foundation for subsequent research into developing natural medicine or modern medications to prevent the extinction of the species.